2023
DOI: 10.1371/journal.pbio.3001964
|View full text |Cite
|
Sign up to set email alerts
|

Control of stereocilia length during development of hair bundles

Abstract: Assembly of the hair bundle, the sensory organelle of the inner ear, depends on differential growth of actin-based stereocilia. Separate rows of stereocilia, labeled 1 through 3 from tallest to shortest, lengthen or shorten during discrete time intervals during development. We used lattice structured illumination microscopy and surface rendering to measure dimensions of stereocilia from mouse apical inner hair cells during early postnatal development; these measurements revealed a sharp transition at postnatal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 101 publications
(235 reference statements)
0
7
0
Order By: Relevance
“…While localization of GPSM2 and GNAI3 was only modestly affected, EPS8 shifted from being primarily found at row 1 tips to being equally distributed between row 1 and 2 tips. We also showed that CDH23 and PCDH15 play an underappreciated role in coordinating the lengths of adjacent stereocilia 28 . Row 1 proteins showed similar altered distribution in Ush1g bw/bw , and adjacent stereocilia lengths were less coordinated, albeit not as profoundly disrupted as in Cdh23 v2J/v2J and Pcdh15 av3J/av3J hair cells.…”
Section: Hair-cell Phenotypementioning
confidence: 69%
See 1 more Smart Citation
“…While localization of GPSM2 and GNAI3 was only modestly affected, EPS8 shifted from being primarily found at row 1 tips to being equally distributed between row 1 and 2 tips. We also showed that CDH23 and PCDH15 play an underappreciated role in coordinating the lengths of adjacent stereocilia 28 . Row 1 proteins showed similar altered distribution in Ush1g bw/bw , and adjacent stereocilia lengths were less coordinated, albeit not as profoundly disrupted as in Cdh23 v2J/v2J and Pcdh15 av3J/av3J hair cells.…”
Section: Hair-cell Phenotypementioning
confidence: 69%
“…Homozygous null mutations in Cdh23 and Pcdh15 lead to altered distribution of proteins that concentrate at the tips of row 1 stereocilia in postnatal hair bundle development 28 . While localization of GPSM2 and GNAI3 was only modestly affected, EPS8 shifted from being primarily found at row 1 tips to being equally distributed between row 1 and 2 tips.…”
Section: Hair-cell Phenotypementioning
confidence: 99%
“…Potential differences in data distribution between genotypes were tested for significance using nested (hierarchical) t-test except for ABR thresholds ( Figure 3 and Figure 3—figure supplement 1 ) where a two-way ANOVA with Sidak’s multiple comparison post hoc test was used. Nested t-tests help avoid pseudoreplication by taking into consideration the data structure, here specifically variance in each animal ( Eisner, 2021 ; Krey et al, 2023 ). OHC half-bundle lengths ( Figure 2G , Figure 2—figure supplement 1G ) were plotted as paired left and right values in the same HC and a potential difference in data variance between genotypes was tested using an F-test.…”
Section: Methodsmentioning
confidence: 99%
“…1) where a 2-way ANOVA with Sidak’s multiple comparison post-hoc test was used. Nested t-tests help avoid pseudoreplication by taking into consideration the data structure, here specifically variance in each animal (Eisner, 2021; Krey et al, 2023). OHC half-bundle lengths (Figure 2G, Figure 2 Supp.…”
Section: Methodsmentioning
confidence: 99%